Integrated analysis of molecular and clinical features associated with overall survival in melanoma patients with brain metastasis - Swaminathan Kumar; Meredith S. Pelster; Merve Hasanov; Renato A. Guerrieri; Courtney W. Hudgens; Debora A. Ledesma; Fuchenchu Wang; Grant M. Fischer; Julie M. Simon; Lauren E. Haydu; Kalman V. Katlowitz; Y. N. Vashisht Gopal; et al. (Acta Neuropathologica Communications)
Abstract Melanoma brain metastases (MBMs) are diagnosed in up to 60% of metastatic melanoma patients. Previous studies have identified clinical factors that correlate with overall survival (OS) after MBM diagnosis. However, molecular and immune features associated with OS are poorly understood. An improved understanding of the molecular and immune correlates of OS could provide insights into MBM patient outcomes and guide therapeutic development. Thus, we analyzed clinical features and outcomes of 74 melanoma patients who underwent surgical resection (via craniotomy) between 1991 and 2015 at our institution with RNA-seq data generated from their MBMs. The median post-operative OS was 8.6 months (range 0.6–146.9). On univariate analysis (UVA), the expression of multiple immune gene signatures was associated with improved OS, including IFN-γ Index, T cell-inflamed and the Expanded Immune Genes. The gene expression signatures of several immune cell types (i.e., T cells, CD8 T cells, cytotoxic lymphocytes, NK cells, monocytes) positively correlated with OS, whereas higher neutrophil gene expression correlated with shorter OS. UVA of clinical features identified low Karnofsky performance score (KPS), elevated serum lactate dehydrogenase (LDH), presence of extracranial metastases (ECMs), and uncontrolled (versus controlled) ECMs as clinical predictors of shorter survival. Multivariate analyses (MVA) were performed with significant clinical factors and all immune features without any redundant highly correlated variables in the model. After backward selection, multivariable coxPH model identified low KPS, low T cell signature, and low monocytic lineage signature as independent predictors of shorter survival. Finally, comparative analysis of MBMs from patients with MBMs only showed that these tumors were characterized by decreased oxidative phosphorylation (OXPHOS) and increased immune infiltration signature versus MBMs from patients with concurrent ECMs. Together these results support the clinical significance of specific immune features of MBMs and suggest their potential use as prognostic biomarkers.